The Effect of Circuit Training on Improvement in Futsal Athletes: Literature Review - Rices Jatra; Sandra Zahara Wati; Alif Rengga Kumara; Muhammad Wahyu Rinaldi; Ricky Fernado (Universitas Majalengka, 2023)
Futsal is a high-intensity, intermittent sport from the beginning to the end of the match. Futsal players must have anthropometric and somatotype characteristics that match the needs of high-intensity intermittent training, as well as good physical condition on the dominant physical aspect, so that players' performance during competition and physiological losses after competition can be minimised to the greatest extent possible. aspects of physical condition as an opportunity for coaches to control player performance through training models. This research is a literature review study that aims to reveal the presence or absence of the influence of circuit training on the improvement of futsal athletes. Using the Google Scholar database, enter the keyword